KELAJAK MADANIYATI: GLOBALLASHUV, TEXNOLOGIYA, YANGI QADRIYATLAR VA MADANIY O‘ZGARISHLAR - Charos Ibragimova Raximovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
As today's world is developing rapidly, culture is not left out of these changes. Globalization, technological advancement, environmental concerns, and new societal values are seen as key factors in shaping future culture. Culture has always adapted to the social, economic and political processes of society, but now it is also looking for answers to the problems of humanity on a global scale. In this article, we will talk about the main directions of the culture of the future, the impact of technological development, new values, and the manifestations of cultural changes.